Response of runoff components to climate change in the source-region of the Yellow River on the Tibetan plateau - Ting Zhang; Li, Dongfeng; Lu, Xixi (Hydrological Processes, 2022)
Abstract Climate change will likely increase the total streamflow in most headwaters on the Tibetan Plateau in the next decades, yet the response of runoff components to climate change and permafrost thaw remain largely uncertain. Here, we investigate the changes in runoff components under a changing climate, based on a high-resolution cryosphere-hydrology model (Spatial Processes in Hydrology model, SPHY) and multi-decadal streamflow observations at the upstream (Jimai) and downstream stations (Maqu and Tangnaihai) in the source-region of the Yellow River (SYR). We find that rainfall flow dominates the runoff regime in SYR (contributions of 48%?56%), followed by snowmelt flow (contributions of 26%/23% at Maqu/Tangnaihai). Baseflow is more important at Jimai (32%) than at the the downstream stations (21%?23%). Glacier meltwater from the Anyê Maqên and Bayankala Mountains contributes negligibly to the downstream total runoff. With increasing temperature and precipitation, the increase in total runoff is smaller in the warm and wet downstream stations than in the cold and dry upstream station. This is because of a higher increase in evapotranspiration and a larger reduction in snowmelt flow in the downstream region in response to a warming climate. With temperature increase, there is less increase in rainfall flow in the downstream region due to increased water loss through evapotranspiration. Meanwhile, the decline in snowmelt flow is larger further downstream, which can negatively impact the spring irrigation for the whole Yellow River basin that supports the livelihoods of 140 million people. Importantly, we find that baseflow plays an increasingly important role in the permafrost-dominated upstream region with atmospheric warming and permafrost thaw, accompanied by decreased surface flow. These findings improve our current understanding of how different hydrological processes respond to climate change and provide insights for optimizing hydropower and irrigation systems in the entire Yellow River basin under a rapidly changing climate.
Keywords: climate change; permafrost thaw; response mechanism; runoff components; source-region of Yellow River